2009
DOI: 10.3109/08860220903125298
|View full text |Cite
|
Sign up to set email alerts
|

Angio-Embolization of Renal Artery Pseudoaneurysm after Renal Biopsy: A Case Report

Abstract: Renal artery pseudoaneurysm is a rare clinical entity that has been reported after renal biopsy, percutaneous renal surgery, penetrating trauma, and rarely blunt renal trauma. We present the case of a 37-year-old man with ruptured renal artery pseudoaneurysm accompanied by massive gross hematuria, urinary clot retention, and bladder tamponade, which were the presenting signs seven hours after renal biopsy. Abdominal CT scan showed a large perinephric, intracapsular hematoma of left kidney. His angiogram reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Signs and symptoms of RAP may develop immediately after the insult or they may be delayed. 6 Hematuria is the most common symptom associated with RAP and results from the erosion of RAP into the adjacent renal collecting system; this may occur within 2 to 4 weeks after the injury. 7 A metaanalysis including 13 studies of partial nephrectomy, which included a total of 105 patients with RAP, showed that 102 (97%) patients were symptomatic at presentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Signs and symptoms of RAP may develop immediately after the insult or they may be delayed. 6 Hematuria is the most common symptom associated with RAP and results from the erosion of RAP into the adjacent renal collecting system; this may occur within 2 to 4 weeks after the injury. 7 A metaanalysis including 13 studies of partial nephrectomy, which included a total of 105 patients with RAP, showed that 102 (97%) patients were symptomatic at presentation.…”
Section: Discussionmentioning
confidence: 99%
“…7 In general, angiographic embolization is the procedure of choice for management of RAP due to its minimally invasive and selective nature and the maximal preservation of renal parenchyma. 6 Renal artery embolization begins with a renal angiogram through a transfemoral approach. Selective embolization of renal artery branches can be achieved by using microcatheters inserted coaxially over a guidewire.…”
Section: Discussionmentioning
confidence: 99%
“…Signs and symptoms of the RAP may develop immediately after the insult or they may be delayed 3. Mima et al 3 reported a case in which massive haematuria, urinary clot rentention and bladder tamponade 7 h after the percutaneous renal biopsy were the presenting signs of RAP.…”
Section: Discussionmentioning
confidence: 99%
“…Signs and symptoms of the RAP may develop immediately after the insult or they may be delayed 3. Mima et al 3 reported a case in which massive haematuria, urinary clot rentention and bladder tamponade 7 h after the percutaneous renal biopsy were the presenting signs of RAP. Haematuria is the most common symptom associated with RAPs and results from erosion of the RAP into the adjacent renal collecting system9; this may occur within 2–4 weeks after the injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation